Knowledge, attitude and practices of mothers of under-five children with acute respiratory tract infection at Queen Elizabeth Central Hospital, Blantyre, Malawi - Suwedi, Chimwemwe Leticia (Kamuzu University of Health Sciences, 2022)
Aim: The aim of this study was to determine knowledge, attitude and practices of mothers of under five children with ARI at QECH, Blantyre, Malawi. The objectives of the study included the assessment mothers' knowledge and recognition of ARI, their practices when children develop symptoms of ARI at home. Determining attitudes of mothers towards ARI and identifying what motivates mothers to seek treatment for ARI with their children. Methodology: It was a qualitative study. Data was collected using an interview guide. The researcher interviewed 10 participants. Data was analyzed manually. Participants included all mothers of under five children with AR_I at special care and nursery wards of paediatric department of QECH. RESULTS: Mothers of under five children with ARI had inadequate knowledge of ARI. There were mixed practices following an illness of their children. Some participants rushed to the hospital while others treated their children at home with left over and over the counter drugs while providing warmth. They did not accent that ARI can be treated by traditional healers. Participants decided to take children to the hospital basing on their own initiative, influence from parents and husband, hope of acquiring standard care and previous experience of better treatment by health personnel at the hospital. Recommendations have been suggested for improvements in nursing practice, nursing management, nursing education and nursing research. It is hoped that efforts will be made to address these issues to ensure mothers of under five children with ARI, seek treatment early for their children to reduce morbidity rate